2016
DOI: 10.1134/s0006297916110134
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokines in the development of atherosclerosis

Abstract: Atherosclerosis contributes to the development of many cardiovascular diseases, which remain the leading cause of death in developed countries. Atherosclerosis is a chronic inflammatory disease of large and medium-sized arteries. It is caused by dyslipidemia and mediated by both innate and adaptive immune responses. Inflammation is a key factor at all stages of atherosclerosis progression. Cells involved in pathogenesis of atherosclerosis were shown to be activated by soluble factors, cytokines that strongly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
181
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(197 citation statements)
references
References 112 publications
2
181
0
14
Order By: Relevance
“…Inflammation and oxidative stress are key factors at all stages of development of atherosclerosis . The origin of the atherosclerotic plaque is initiated and sustained by the combined endothelial dysfunction caused by chronic exposure to factors that promote vascular inflammation, such as hyperlipidemia, hypertension, smoking, and diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and oxidative stress are key factors at all stages of development of atherosclerosis . The origin of the atherosclerotic plaque is initiated and sustained by the combined endothelial dysfunction caused by chronic exposure to factors that promote vascular inflammation, such as hyperlipidemia, hypertension, smoking, and diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of pro-inflammatory cytokines (e.g., MCP-1, TNF-α and IL-6) in the initiation and progression of AT is well documented [8, 28, 65-67]. However, there are many challenges when studying the immune system in mice aortic tissues, due to the size and the number of cells obtained from the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MCP-1 plays an important role in the recruitment and trans-endothelial migration of monocytes in early atherogenesis [1, 71, 72]. At the same time, IL-6 is an important biomolecule that increases the oxidative stress, promotes fatty streaks and induces leukocytes recruitment into the sub-endothelial space [65, 73]. This led us to propose that the reduction of pro-inflammatory mediators by sildenafil might be justified by an increase in cGMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerosis is a common inflammatory vascular disease worldwide, which is associated with high morbidity and mortality . Endothelial cell dysfunction and damage evoked by reactive oxygen species (ROS) is central in the pathogenesis of atherosclerosis .…”
Section: Introductionmentioning
confidence: 99%